O ENSINO DE BIOLOGIA E A INCLUSÃO ESCOLAR: O OLHAR DE UMA PROFESSORA/PESQUISADORA - Leni Coleti Novaes Gomes Cerqueira (2024)
The present investigation is linked to the research line “Education, Childhoods, and Diversities” within the Stricto Sensu Graduate Program in Education at the Federal University of Mato Grosso do Sul (UFMS), Três Lagoas. It was conducted at the Center for Studies and Research in Inclusion (NEPI). The objective was to understand how Biology teachers in the state education system of a municipality in the State of São Paulo teach based on their knowledge of school inclusion. The study involved three Biology teachers from the State Education network, all affiliated with the Teaching Department of Mirante do Paranapanema-SP. Data was collected through two discussion rounds via Google Meet and analyzed interpretatively through narrative construction. From the data study, it was possible to conclude that the participating Biology teachers have doubts about the inclusive concept of education. They perceive inclusion as merely integrating special education target students into regular schools. Often, this leads to adapting activities for specific students, which we consider an exclusive practice. Inclusive teaching should involve varied activities for all, not adaptations for some. Additionally, the teachers adapt activities because they believe it’s the best practice, influenced by their training from the education network. Consequently, they plan lessons for some students and then adapt them for others, specifically students in Special Education. Despite associating inclusion only with certain students (those within the Special Education target group), in practice, when teachers don’t target specific groups, they can develop teaching that allows everyone to participate according to their abilities. The biology teachers express a need for ongoing training in inclusion and better alignment between school management and education secretaries so that these higher bodies align with inclusive principles and understand each school’s real challenges.